2019
DOI: 10.3846/bme.2019.10512
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Learning Strategies and Performance Among Business Undergraduates at University Colleges in Sweden

Abstract: Purpose – This paper brings new material to the understanding of interlinkages between motivation, learning and performance in academic contexts. By investigating these interlinkages in a new context – students of business and management at a Swedish university college – it seeks to answer the following research questions: How do students’ degree and type of motivation relate to their learning strategies?; how do students’ degree and type of motivation and learning strategies relate to their academic success?;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…According to the results of the research, surface approach means of the students are higher than those of strategic and deep approach. This may stem from the fact that assessments and grades are geared toward surface learning, as the surface-type of learning approach is more suitable for exam success (Bengtsson & Teleman, 2019). Another finding suggests that the surface learning approach preferences of pre-service teachers does not differ according to gender.…”
Section: Discussionmentioning
confidence: 98%
“…According to the results of the research, surface approach means of the students are higher than those of strategic and deep approach. This may stem from the fact that assessments and grades are geared toward surface learning, as the surface-type of learning approach is more suitable for exam success (Bengtsson & Teleman, 2019). Another finding suggests that the surface learning approach preferences of pre-service teachers does not differ according to gender.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, in our study, we predicted that Polish first-year female students would also outperform men in the case of learning strategies (H2) and self-regulation (H3) [2], and would declare higher test anxiety (H4). A further study revealed that female students are more intrinsically motivated [31]. According to Velayutham et al [15] in relation to 719 boys and 641 girls across grades 8, 9, and 10 in 5 public schools in Perth, Western Australia, the influence of task on self-regulation was statistically significant for men only.…”
Section: Sex Differences In Msl Factorsmentioning
confidence: 90%
“…Moreover, this trend is present when these students have become professionals/employees [ 52 , 67 , 68 , 69 ]. These findings suggest that securing a prestigious and highly salaried position is the primary driver for choosing a business education programme [ 70 ], whereas healthcare students are more likely to study a healthcare subject out of personal interest or enjoyment [ 35 ], leading to improved learning outcomes. These characteristics were deemed similar (a) between online and face-to-face education, and (b) between pre-graduation and post-graduation.…”
Section: Discussionmentioning
confidence: 99%